Let's Not Jump to Conclusions: Approaching Felon Disenfranchisement Challenges Under the Voting Rights Act - Varnum, Thomas G. (2008)
Section 2 of the Voting Rights Act of 1965 invalidates voting qualifications that deny the right to vote on account of race or color. This Article confronts a split among the federal appellate courts concerning whether felons may rely on Section 2 when challenging felon disenfranchisement laws. The Ninth Circuit Court of Appeals allows felon disenfranchisement challenges under Section 2; however, the Second and Eleventh Circuits foresee unconstitutional consequences and thus do not. After discussing the background of voting rights jurisprudence, history of felon disenfranchisement laws, and evolution of Section 2, this Article identifies the points of contention among the disagreeing courts. The crux of this Article is that both sides of the debate have erred. Both sides wrongly assume that the consequences of accepting these vote denial challenges are predictable. However, because a standard approach to vote denial challenges under Section 2 does not currently exist, no court can foresee the results of allowing such challenges to felon disenfranchisement laws. Therefore, predicting the constitutional implications of accepting these challenges without first identifying an appropriate analysis is impossible. This Article concludes by proposing an analysis for consideration. The proposed approach is a tailored version of sliding scale scrutiny--an analysis that the United States Supreme Court following Burdick v. Takushi, now applies to constitutional voting rights claims. Using this adapted approach, the Supreme Court can resolve the current split in authority and find that Section 2 is a viable vehicle for challenging racially-discriminatory felon disenfranchisement laws